What's on their mind: do exchange rate forecasters stick to theoretical models? - Michael Schröder; Robert Dornau (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
Do financial market analysts use structural economic models when forecasting exchange rates? This is the leading question analysed in this paper. In contrast to other studies we use expectations data instead of observable variables. Therefore we analyse the implicit structural models forecasters have in mind when forming their exchange rate expectations. The economic exchange rate models included in our study are purchasing power parity, the flexible-price monetary model, the sticky-price monetary model and the Mundell-Fleming model. These models are the theoretical basis for the estimation of latent structural models using the categorical expectations data of the ZEW financial market survey. The expectation variables used to explain expected exchange rates are short term interest rates, long term interest rates and business expectations. Our results show that the flexible-price monetary model is clearly rejected, but the sticky-price monetary model (in case of DM/Pound Sterling and DM/Yen) and the Mundell-Fleming model (in case of DM/US-Dollar) are both compatible with the estimated parameters.
Keywords: C35; F31; 330; Exchange rate modelling; Expectations; Survey data; Categorical Data; Wechselkurs; Rationale Erwartung; Wertpapieranalyse; Wechselkurstheorie; Schätzung; Deutschland